Indian Ocean migrants and state formation in Hadhramaut : reforming the homeland - Freitag, Ulrike (Social, economic, and political studies of the Middle East and Asia, 2003)
Based on Hadhrami and British sources, as well as on fieldwork in Yemen and Indonesia, this text traces the ways in which members of the diaspora and travellers interacted with the homeland through their remittances, political initiatives and the introduction of new ideas and institutions.